Extended Medicaid coverage will improve access but insufficient to enhance postpartum care utilization: a secondary analysis of the 2016–2019 Arizona Medicaid claims - Okechukwu, Abidemi; Abraham, Ivo; Okechukwu, Chinedu; Magrath, Priscilla; Marrero, David G.; Farland, Leslie V.; Alaofe, Halimatou (Frontiers in Public Health, 2024)
Introduction Postpartum Medicaid eligibility extensions may increase access to healthcare for low-income women. However, its implications for healthcare utilization are unknown. Methods We analyzed the linked-infant birth certificate and claims data of women whose childbirths were paid for by Medicaid between 2016 and 2019 in Arizona, United States. We evaluated associations between postpartum care visits and Medicaid insurance type and assessed effect modification by the delivery route and type of residence. Results Women with pregnancy-related Medicaid insurance were less likely to attend postpartum visits, with an adjusted odds ratio (aOR) of 0.70 and a 95% confidence interval (CI) of 0.66 to 0.74 than those with continuous Medicaid insurance. Younger age, rural residence [aOR 0.83, CI 0.78, 0.88], vaginal delivery route [aOR 0.11, CI 0.10, 0.12], and the absence of complications during/after childbirth [aOR 0.58, CI 0.49, 0.70] were associated with the absence of postpartum care visit. Low-income women who lost their pregnancy-related Medicaid coverage after 60 days in Arizona experienced lower rates of postpartum care utilization. Discussion Interventions to improve postpartum utilization should be considered beyond extending postpartum Medicaid coverage for low-income women.